Strengthening Religious Literacy in the Higher Education Curriculum in Ajatappareng - Syawal Syawal; Andi Ahmad Chabir Galib; Ismaya Ismaya (Edumaspul: Jurnal Pendidikan, 2024)
Religious literacy is the ability to understand, internalize, and practice religious teachings contextually while respecting diversity. Amid the flow of digital information and the rise of intolerance, strengthening religious literacy in higher education has become increasingly important. This study aims to explore how religious literacy is reinforced in the higher education curriculum in the Ajatappareng region and its impact on shaping students' moderate character. This research adopts a descriptive qualitative approach using case study methods at several public and private universities in the Ajatappareng area. Data were collected through in-depth interviews, document studies (syllabi, lesson plans, academic guidelines), and analyzed thematically. The results show that religious literacy is reinforced through the integration of moderate religious values into teaching materials, contextual learning approaches, and student involvement in religious activities that foster tolerant attitudes. Challenges include the lack of learning innovation, the dominance of cognitive approaches, and limited training for lecturers on multicultural-based religious literacy. The implication is that the religious education curriculum needs to be reformulated not only theologically, but also equipping students with critical, empathetic, and dialogical thinking skills to help build an inclusive and peaceful society.